Analysis of breath volatile organic compounds in children with chronic liver disease compared to healthy controls. (20th April 2015) - Eng, Katharine; Alkhouri, Naim; Cikach, Frank; Patel, Nishaben; Yan, Chen; Grove, David; Lopez, Rocio; Rome, Ellen; Dweik, Raed A
Abstract: Breath testing is increasingly being used as a non-invasive diagnostic tool for disease states across medicine. The purpose of this study was to compare the levels of volatile organic compounds (VOCs) as measured by mass spectrometry in healthy children and children with chronic liver disease (CLD). Patients between the ages of 6 and 21 were recruited for the study. Control subjects were recruited from a general pediatric population during well-child visits, while patients with CLD were recruited from pediatric gastroenterology clinic visits. The diagnosis of CLD was confirmed by clinical, laboratory, and/or histologic data. A single exhaled breath was collected and analyzed by means of selected-ion flow-tube mass spectrometry per protocol. A total of 104 patients were included in the study (49 with CLD and 55 healthy controls). Of the patients with CLD, 20 had advanced liver fibrosis (F3–F4). In the CLD cohort, levels of exhaled 1-decene, 1-heptene, 1-octene and 3 methylhexane were found to be significantly higher when compared to the control population ( p  < 0.001, p = 0.035, p  < 0.001 and p = 0.004, respectively). Exhaled 1-nonene, (E)-2-nonene, and dimethyl sulfide levels were found to be significantly lower in patients with CLD patients when compared to controls ( p  < 0.001, p  < 0.001 and p = 0.007, respectively). By utilizing a combination of five of the VOCs, the accuracy for predicting the presence of CLD was excellent (AUROC = 0.97). Our study demonstrates that children with CLD have a unique pattern of exhaled VOCs. Utilization of a combination of these VOCs represents a promising non-invasive diagnostic tool and may provide further insight into the pathophysiologic processes and pathways leading to pediatric liver disease. Further analysis of these compounds in external cohorts are needed to validate our findings.